Milk Production of Friesian Holstein Cows During the First Month Postpartum as Affected by Depolarized Katuk Supplement - Afton Atabany; Agik Suprayogi; Muladno Muladno; Fadjar Satrija; Ronald Tarigan; Farida Ratna Dewi; Welly Sugiono; Yuliantony Queen; Tras Amboro (Jurnal Ilmu Pertanian Indonesia, 2026)
This study included 21 recently calved FH cows divided into three treatment groups: control (P0), depolarized katuk (Sauropus androgynus) leaf powder (P1), and depolarized katuk leaf pellet (P2). The study found that the dry matter intake for treatment P0, P1, and P2 were 15.59 ± 0.91 kg, 15.14 ± 1.38 kg, and 16.27 ± 1.28 kg, respectively. Milk production in these three different treatments were 25.91±5.94 L, 23.80±3.42 L, and 32.11±4.75 L, respectively. The dry matter percentage of milk (total solid) in P0 was 21.75±11.67%, P1 was 21.7±0.99%, and P2 was 31.0±10.75%. Depolarized katuk leaves, particularly in pellet form, resulted in much higher milk production than the control group. These data suggest that feeding depolarized katuk leaves as a supplementary feed to FH dairy cows can improve milk supply and quality during the first month of lactation. The inclusion of depolarized katuk leaves, particularly in pellet form, may be a useful technique for increasing dairy cattle productivity and health. Keywords: friesian holstein, depolarized katuk leaves, milk quality, 1-month lactation, milk production